Understanding the experiences of caregivers of HIV-exposed children under five: A phenomenological inquiry - Happy Hayati; Nani Nurhaeni; Dessie Wanda; Nuraidah Nuraidah (Belitung Nursing Journal, 2023)
Background: Children born to mothers with HIV require special care from the womb to the postnatal period, and caregivers involved in their care face several challenges. Objective: This study aimed to explore caregivers’ experiences providing care for HIV-exposed children under five. Methods: This study employed a phenomenological approach. Ten caregivers of HIV-exposed children living in Jakarta, Indonesia, were selected using snowball techniques. Online in-depth interviews were conducted to collect data from September 2021 to July 2022, and thematic analysis using Colaizzi’s method was performed for data analysis. Results: The study involved ten caregivers (nine females and one male) aged between 23 and 42 years. Seven of them were mothers who tested HIV-positive, while one was an adoptive father, one was a mother’s sister, and one was an aunt of HIV-exposed children. The majority of them were housewives and had a low educational background. Three themes were generated: (i) disease-transmission foreboding, (ii) prejudice against mothers and children exposed to HIV, and (iii) seeking support. Conclusion: Caring for HIV-exposed children poses emotional and physical challenges for caregivers, necessitating support from health professionals and peer groups. Nurses play essential roles in improving caregiver well-being and supporting optimal growth and development in HIV-exposed children under five by designing intervention programs. Furthermore, to enhance home-based HIV care in Indonesia, the government must implement social interventions that target families with limited resources.